2023
DOI: 10.1021/jacs.3c01225
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Conventional Limitation of Photocycloaddition Reaction in the Roomy Nanospace of a Metal–Organic Framework

Abstract: Topochemical reactions provide selective products based on the molecular position; however, they generally require molecules to be placed in strictly limited orientations and distances, making them less versatile. In this study, we found that by confining trans-4-styrylpyridine (4spy) as a reactive substrate in a flexible metal−organic framework (MOF) nanospace, [2+2] cycloadducts can be selectively obtained, even when the distance between two C�C bonds of 4-spy in the crystal is 5.9 Å, which is much larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…13 On this basis, other photopolymerization-driven polyvinyl alcohol composite film and stilbene-based Zn 2 ðsdcÞ 2 (sdc =4,4′-stilbenedicarboxylate) MOF film have also been reported by Lang and Gu and others. [89][90][91] As aforementioned, stimuli-responsive fluorescent MOFs have broad application prospects in security protection fields, such as information encryption and anticounterfeiting displays, mainly due to their ability to successfully prevent information or data from being stolen, mimicked, or forged. 92,93 Among them, the biggest advantage of light-responsive MOFs is that their chemical and structural changes can be regulated through light stimulation, providing an alternative way for constructing MOFs with switchable optical absorption and fluorescence properties.…”
Section: Benefits Of Stimuli-responsive Photonic Mofsmentioning
confidence: 99%
“…13 On this basis, other photopolymerization-driven polyvinyl alcohol composite film and stilbene-based Zn 2 ðsdcÞ 2 (sdc =4,4′-stilbenedicarboxylate) MOF film have also been reported by Lang and Gu and others. [89][90][91] As aforementioned, stimuli-responsive fluorescent MOFs have broad application prospects in security protection fields, such as information encryption and anticounterfeiting displays, mainly due to their ability to successfully prevent information or data from being stolen, mimicked, or forged. 92,93 Among them, the biggest advantage of light-responsive MOFs is that their chemical and structural changes can be regulated through light stimulation, providing an alternative way for constructing MOFs with switchable optical absorption and fluorescence properties.…”
Section: Benefits Of Stimuli-responsive Photonic Mofsmentioning
confidence: 99%
“…Comparing the two structures before and after the [2 + 2] photocycloaddition reaction, the students should observe the formation of the cyclobutane derived from pairs of CC bonds (Figure ). It is important to engage students in the discussion of the potential reason for the cyclobutane formation of the CC bonds, which may be due to the fact that the pedal motion in the crystal structure brings the CC bonds of adjacent 4-npy ligands parallel to each other so that a photochemical [2 + 2] cycloaddition can occur. …”
Section: Description Of the Experimentsmentioning
confidence: 99%
“…Olefinic coordination polymers (CPs) have received extensive attention due to their intriguing photochemical reactivity and their potential applications in fluorescence, molecular/ion sensing, gas adsorption, , magnetism, molecular switch and so on. By means of coordination-bond templates, a large number of mono/di/tri/tetra-olefinic CPs with different topological structures have been constructed and researched for [2 + 2] photocycloaddition reactions to date.…”
Section: Introductionmentioning
confidence: 99%
“…53 However, not all of these CPs can favorably S2). Upon exposure to the visible light (495 nm) within or above 48 h (Table S2), 1 H NMR spectra revealed that these photoreactive CPs got dimerized into the cyclobutane photoproducts with different conversion ratios of 48% (1, Figure S19), 32.4% (2, Figure S21), 87.5% (5, Figure S23), and 45.6% (6, Figure S25). There were different conversions into monocyclobutane products for these four CPs due to structural differences.…”
Section: ■ Introductionmentioning
confidence: 99%